Restenosis after carotid artery stenting. (December 2017) - Dai, Zhengze; Xu, Gelin
As a common etiology for ischemic stroke, atherosclerotic carotid stenosis has been targeted by vascular surgery since 1950s. Compared with carotid endarterectomy, carotid angioplasty and stenting (CAS) is almost similarly efficacious and less invasive. These advantages make CAS an alternative in treating carotid stenosis. However, accumulative evidences suggested that the long-term benefit-risk ratio of CAS may be decreased or even neutralized by the complications related to in-stent restenosis (ISR). Therefore, investigating the mechanisms and identifying the influential factors of ISR are of vital importance for improving the long-term outcomes of CAS. As responses to intrinsic and extrinsic injuries, intimal hyperplasia and vascular smooth muscle cell proliferation have been regarded as the principle mechanisms for ISR development. Due to the lack of consensus-based definition and consistent follow-up protocol, the reported incidences of ISR after CAS varied widely among studies. These variations made the inter-study comparisons of ISR largely illogical. To eliminate restenosis after CAS, both surgery and endovascular procedures have been attempted with promising results. For preventing ISR, drug-eluting stents and antiplatelets have been proposed as potential solutions.